Conservadorismo e serviço social : da relação embrionária a intenção de ruptura - Pereira, Bruna Fernanda Bólico (2015)
This work aims to analyze the presence of conservatism in the Brazilian Social Service. For this a literature search was performed. We seek to understand the classic conservative ideology, and its meaning with the advent of modernity, as well as opposition to conservatism and resistance that was established with the Marxist dialectic. We go through the historical moment that emerges of social workers to the search process to break with traditionalism. And then we enter in the contemporary world in order to identify the main ways that reactualized conservatism and neoconservatism in Social Work. He tried to even have clarity of the challenges facing the profession in order to throw himself to his face.